Seismic Tomographic Imaging of the Eastern Mediterranean Mantle: Implications for Terminal‐Stage Subduction, the Uplift of Anatolia, and the Development of the North Anatolian Fault. (21st July 2020) - Kounoudis, R.; Bastow, I. D.; Ogden, C. S.; Goes, S.; Jenkins, J.; Grant, B.; Braham, C.
Abstract: The Eastern Mediterranean captures the east‐west transition from active subduction of Earth's oldest oceanic lithosphere to continental collision, making it an ideal location to study terminal‐stage subduction. Asthenospheric‐ or subduction‐related processes are the main candidates for the region's ∼2 km uplift and Miocene volcanism; however, their relative importance is debated. To address these issues, we present new P and S wave relative arrival‐time tomographic models that reveal fast anomalies associated with an intact Aegean slab in the west, progressing to a fragmented, partially continental, Cyprean slab below central Anatolia. We resolve a gap between the Aegean and Cyprean slabs, and a horizontal tear in the Cyprean slab below the Central Anatolian Volcanic Province. Below eastern Anatolia, the completely detached "Bitlis" slab is characterized by fast wave speeds at ∼500 km depth. Assuming slab sinking rates mirror Arabia‐Anatolia convergence rates, the Bitlis slab's location indicates an Oligocene (∼26 Ma) break‐off. Results further reveal a strong velocity contrast across the North Anatolian Fault likely representing a 40–60 km decrease in lithospheric thickness from the Precambrian lithosphere north of the fault to a thinned Anatolian lithosphere in the south. Slow uppermost‐mantle wave speeds below active volcanoes in eastern Anatolia, and ratios of P to S wave relative traveltimes, indicate a thin lithosphere and melt contributions. Positive central and eastern Anatolian residual topography requires additional support from hot/buoyant asthenosphere to maintain the 1–2 km elevation in addition to an almost absent lithospheric mantle. Small‐scale fast velocity structures in the shallow mantle above the Bitlis slab may therefore be drips of Anatolian lithospheric mantle. Plain Language Summary: Before continental tectonic plates collide, the oceanic plate between them must complete the process of subduction. However, precisely how slabs ultimately detach and sink into the deep mantle is debated. The Eastern Mediterranean is a unique natural laboratory for terminal subduction processes: It captures the transition from subduction of Earth's oldest oceaniclithosphere in the west to collision‐dominated convergence in the east. Using the seismograms of distant earthquakes, we image mantle structure beneath Anatolia using P and S wave traveltime tomography. Several stages of subduction zone maturity are revealed, with an intact sinking plate in the west transitioning to a completely detached one in the east. Our tomographic models illuminate horizontal and vertical slab tears that correlate with volcanoes above. We suggest subduction in eastern Anatolia terminated ∼26 Ma, meaning the region's youngest (10 Ma to present) volcanism there is largely unrelated to classic, slab‐dehydration processes. Instead, when reviewed in light of Anatolia's thin lithosphere and hot, partially molten asthenosphere, the region's youngest volcanoes are likely the result of removal, or delamination, of dense lower‐plate material, which is now sinking into the mantle above denser, colder, oceanic African plate. Key Points: The 500 km‐deep Bitlis slab agrees with break‐off ∼26 Ma; thus, 10 Ma to present lavas may relate to lithospheric removal Slow anomalies, <100 km deep, imply thin lithosphere, solidus‐exceeding temperatures, and mantle melt below central and eastern Anatolia Contrasts across the North AnatolianFault are caused by juxtaposed Precambrian lithosphereand asthenosphere beneath thin Anatolian lithosphere